Resveratrol Delivery by Albumin Nanoparticles Improved Neurological Function and Neuronal Damage in Transient Middle Cerebral Artery Occlusion Rats - Huae Xu; Ye Hua; Jie Zhong; Xiaolin Li; Wei Xu; Yingyuan Cai; Yukang Mao; Xiaowei Lu (Frontiers Media S.A., 2018)
Human serum albumin (HSA) is an intrinsic protein and important carrier that transports endogenous as well as exogenous substances. It is demonstrated in this study that the regional accumulation of albumin in the ischemia-reperfusion (I/R) brain may lead in the application of HSA based nanoparticles in the study of cerebral I/R injury. Resveratrol (RES) is potential in the treatment of cerebral I/R injury but is restricted for its water insolubility and short half-life in vivo. In our study, RES loaded HSA nanoparticles (RES-HSA-NPs) were prepared to facilitate the application of RES in protection from cerebral I/R injury. RES-HSA-NPs demonstrated spherical shape, a diameter about 100 nm, a highest RES encapsulation efficiency of 60.9 ± 5.07%, and controlled release pattern with the maximum release ratio of 50.2 ± 4.91% [in pH = 5.0 phosphate buffered saline (PBS)] and 26. 2 ± 2.73% (in pH = 7.4 PBS), respectively, after 90 h incubation at 37°C. After intravenous injection into transient middle cerebral artery occlusion (tMCAO) rats, RES-HSA-NPs improved neurological score and decreased infarct volume at 24 h after tMCAO in a dose dependent manner. A single dose of 20 mg/kg RES-HSA-NPs via tail vein improved neurological outcomes and decreased infarct volume at 24 and 72 h in tMCAO rats. I/R increased oxidative stress (indicated by products of lipid peroxidation, MDA) and neuronal apoptosis (indicated by yellow-brown TUNEL-positive cells), RES-HSA-NPs significantly attenuated oxidative stress and neuronal apoptosis. These results demonstrated the potential of RES-HSA-NPs in the therapy of cerebral I/R injury.